A dyadic analysis of stress processes in Latinas with breast cancer and their family caregivers. Issue 3 (28th November 2017) - Segrin, Chris; Badger, Terry A.; Sikorskii, Alla; Crane, Tracy E.; Pace, Thaddeus W.W.
Abstract: Objective: Breast cancer diagnosis and treatment negatively affect quality of life for survivors and their family caregivers. The stress process model has been useful for describing the cascade of social and psychological experiences that culminate in degraded quality of life for both survivors and their family caregivers. This study is designed to test theoretically specified predictors of negative psychosocial outcomes in a dyadic context. Methods: Participants were 230 dyads composed of Latinas recently diagnosed with breast cancer and their primary family caregiver, who completed measures of socioeconomic status, stress, family conflict, depression, and anxiety. Data were analyzed following the Actor‐Partner Interdependence Mediation Model in structural equation modeling. Results: For both survivors and caregivers, there were significant direct and indirect actor effects (through family conflict) of perceived stress on depression and anxiety. Several indirect partner effects were also evident in this sample. Specifically, caregivers' stress was predictive of survivors' depression and anxiety through survivors' increased perceptions of family conflict. Conclusions: As predicted by the stress process model, stress and family conflict were predictive of psychological distress in breast cancer survivors and their family caregivers. Significant partner effects in the Actor‐Partner Interdependence Mediation Model suggest that there are some dyadic influences, particularly from caregivers' stress to survivors' perceptions of exacerbated family conflict. These findings show how strained family relationships can aggravate the well‐being of cancer survivors and their family caregivers through this challenging experience.